2009
DOI: 10.1007/s11430-009-5017-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of biodegradation on the compositions of aromatic hydrocarbons and maturity indicators in biodegraded oils from Liaohe Basin

Abstract: Citation: Bao J P, Zhu C S. The effects of biodegradation on the compositions of aromatic hydrocarbons and maturity indicators in biodegraded oils from Liaohe Basin. By the aid of GC-MS technique, a series of sequentially biodegraded oils from Liaohe Basin have been analyzed. The results show that the concentrations and relative compositions of various aromatic compounds in the biodegraded crude oils will change with increasing biodegradation degree. The concentrations of alkyl naphthalenes, alkyl phenanthrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The serious biodegradation for some oils may also lead to the great variations of FLs, DBTs and DBTs composition. Bao and Zhu (2009) reported that DBT/PHEN ratios increase with the increasing degree of biodegradation of crude oils in the Western Depression. Therefore, the influence of biodegradation can not be excluded.…”
Section: The Application Of Ternary Diagram Of Fls Dbts and Dbfs In mentioning
confidence: 99%
“…The serious biodegradation for some oils may also lead to the great variations of FLs, DBTs and DBTs composition. Bao and Zhu (2009) reported that DBT/PHEN ratios increase with the increasing degree of biodegradation of crude oils in the Western Depression. Therefore, the influence of biodegradation can not be excluded.…”
Section: The Application Of Ternary Diagram Of Fls Dbts and Dbfs In mentioning
confidence: 99%
“…In the two-ring naphthalene series ( Figure 3 ), as the number of methyl substituents increased from 0 to 5, the effect of illite varied from inhibition (0, 1, 2) to stimulation (3, 4) and then, to inhibition (5) ( Figure S9 ). In general, with an increase in the number of methyl substituents, the steric hindrance, stability, and biodegradation resistance of naphthalene series compounds increase [ 64 , 65 , 66 , 67 ]. However, the effect of illite on the biodegradation of naphthalene series compounds was not consistent with this rule, and this phenomenon of altered influence with the increase in the methyl substitution number of naphthalene series was also exhibited by Mon [ 36 ] ( Figure S14 ).…”
Section: Resultsmentioning
confidence: 99%
“…PAHs have been applied as molecular maturity parameters on the basis of the different thermodynamic stabilities of individual isomers, for example, MDR = 4-methylDBT/1-methylDBT, DMDBTI = (4,6-+2,4-DMDBT)/(1,4-+1,6+1,8-+4,6-+2,4-DMDBT), TMDBTI = 2,4,6-TMDBT/(2,4,7-+2,4,8-TMDBT), MCI1 = 1.5 × (2-MChy + 3-MChy)/(chrysene + 1-MChy + 4-MChy + 5-MChy + 6-MChy), MPYR [2-MPy/(2-MPy + 1-MPy)], TAS = (C 20 + C 21 triaromatic steroids)/(C 20 + C 21 + C 26 + C 27 + C 28 triaromatic steroids), C 28 TAS = C 28 triaromatic steroid 20S/(20S + 20R) . In addition, PAHs are also applied to oil–oil/source rock correlation, depositional environment reconstruction, and oil migration pathway tracing. , For example, it is well accepted that the relative abundance of dibenzothiophenes is largely controlled by depositional conditions, and it can serve as a good indicator to distinguish depositional environments and correlate oils . However, secondary alteration processes, such as biodegradation and water washing, can also change the content and composition of PAHs in crude oils, resulting in the failure of geochemical indicators.…”
Section: Introductionmentioning
confidence: 99%